Metformin-related lactic acidosis with acute kidney injury: results of a French observational multicenter study. (3rd May 2020) - Corchia, Anthony; Wynckel, Alain; Journet, Julien; Moussi Frances, Julie; Skandrani, Nihel; Lautrette, Alexandre; Zafrani, Lara; Lewandowski, Elisabeth; Reboul, Pascal; Vrigneaud, Laurence; Djerada, Zoubir; Rieu, Philippe
Abstract: Background: Metformin-associated lactic acidosis (MALA) and metformin-induced lactic acidosis (MILA) remain controversial entities. Metformin toxic effect depends on accumulation to lead to lactic acidosis (LA), particularly during an episode of acute kidney injury (AKI). In MILA, no other condition contributing to LA is found. The aims of this study were to describe the characteristics and prognosis of AKI associated with LA in metformin users and to clarify the role of this drug in the different types of LA. Methods: We performed a French multicenter retrospective study in diabetic patients treated by metformin presenting with LA in a context of AKI in 2015. 126 nephrology units (NU) and 23 intensive care units (ICU) were contacted. We individualized MILA and MALA patients in order to illustrate the role of metformin. Results: We included 173 patients (109 MILA, 64 MALA). 103 patients presented without hemodynamic instability (82 MILA and 21 MALA) whereas 70 patients were shocked including 27 MILA. The shock was associated with death with an odds ratio (OR) of 12.92 ( p  < .001). Digestive disorders (DD) were strongly associated with MILA ( p  = .0001). MALA was significantly associated with shock ( p  < .0001). The mortality rate was higher in MALA (26%) when compared with MILA (7%). Dialysis performed in 133 patients was significantly associated with shock, kalemia, lactate and serum creatinine levels. In multivariate analysis, metformin level was independently associated with pH or lactate level only in MILA patients. Conclusions: MILA is associated with DD and death is due to severe refractory acidosis leading to cardiovascular collapse attributed to metformin accumulation mainly via AKI. MALA patients are more frequently shocked and death is related to their underlying condition, metformin accumulation increasing LA.